THE EFFECT OF ORGANIZATIONAL CULTURE AND WORK DICIPLINE ON LECTURERS PERFORMANCE IN UNDHARI - Alex Ferdinal; Kelik Purwanto; Fenisi Resty (Universitas Islam Lamongan, 2023)
The purpose of this study is to analyze the effect of organizational culture and work dicipline on lecturers performace in University of Dharmas Indonesia (UNDHARI). Survey and questionaires was used to collect data study from 82 respondents as sample study. Simple linier regression test was used as data analysis, and coefficient determination test (R2) and partial test (t-test) conducted to test the hyphotesis, with SPSS.20 as a tool in data processing. The result showed there is a positive and significant effect of organizational culture (X1) on lecturers performace (Y), and also there is a positive and significant effect of work dicipline (X2) on lecturers performance (Y). The result also showed both organizational culture and work dicipline simultaneouly effect lecturers performance in University of Dharmas Indonesia (UNDHARI). This was proven by the significant value 0,000 ( under 0,05). Value of coefficien determination (R2) in linier regression was 72,6 percent. Value of coefficient determination indicates that changes in Y variable (performace) explained by organizational culture (X1) and work dicipline (X2), as the rest explained by other variables